Analisis Pemilihan Supplier dengan Pendekatan Analytical Hierarchy Process di PT. ABC - Agraeni, Rosalia; Gustian, Dudih (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Suppliers are one of the most important parts of a company. For maximum production results, the company also needs suppliers with the best quality. Therefore, companies need a decision support system that can assist in accurate supplier selection based on specified criteria. This supplier selection process uses the Analytic Hierarchy Process (AHP) approach, which is usually a method of ranking decision alternatives and selecting the best option from a number of criteria. The criteria for selecting this supplier are quality, delivery, service and suitability of goods